2022
DOI: 10.3390/en15145002
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Carbon Emission from Household Consumption Based on LMDI and SDA Model: A Decomposition and Comparison Analysis

Abstract: Household consumption has become an important field of carbon dioxide emissions. Urban–rural disparity in the household carbon emissions (HCEs) of residents and their influencing factors are relevant to HCE reduction. Taking Fujian as the study area, the LMDI and SDA models were used to analyze the effects of influencing factors for the direct household carbon emissions (DHCEs) and indirect carbon emissions (IHCEs) of urban and rural residents from 2006 to 2018. The HCEs continue to rise, approximately 65% fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…To examine the causes of energy consumption and household socio-economic factors on CO 2 emissions, a wide range of studies have used various methodologies 40 43 . Verified the impacts of economic growth, population, and energy expenditure on household CO 2 emissions in the framework of the LMDI decomposition model.…”
Section: Methodsmentioning
confidence: 99%
“…To examine the causes of energy consumption and household socio-economic factors on CO 2 emissions, a wide range of studies have used various methodologies 40 43 . Verified the impacts of economic growth, population, and energy expenditure on household CO 2 emissions in the framework of the LMDI decomposition model.…”
Section: Methodsmentioning
confidence: 99%
“…A first motivation for including behavioural advice in national climate policies aimed at reducing GHG emissions consists in spreading the idea that the actors involved in the fight against climate change are not only large energy companies and productive realities in general, but that even an individual citizen has tangible responsibilities towards the planet. Considering that since 1990, the energy consumption in the residential sector of some developed countries has exceeded that in the industrial sector, highlights the role of households as an important source of carbon emissions (Chen, Lin, & Wang, 2022). Moreover, carbon emissions from household consumption practices are not only generated directly, for example through the transportation of people or the residential heating, but also indirectly, for example in the products or foods purchased: therefore, it is essential to raise awareness also of these indirect emissions (e.g.…”
Section: To Raise the Awareness Of Every Citizenmentioning
confidence: 99%
“…The results showed that there is strong spatial heterogeneity in the estimated elasticity coefficients. Chen et al [29] studied the effects of influencing factors on direct household carbon emissions and indirect carbon emissions of urban and rural households in Fujian province by using LMDI and SDA models. (3) In China, gray correlation analysis is frequently used to investigate the correlation degree between the influencing factors of carbon emissions and carbon emissions.…”
Section: Introductionmentioning
confidence: 99%